Inclusive Islamic Education From The Perspective of Tariq Ramadan: An Integrative Strategy for Bridging Gaps in The Islamic Education Curriculum - Anis Sukmawati; Ali Mas'ud; M. Yunus Abu Bakar; Dulyawit Naknawa (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2026)
This article aims to examine the concept of inclusive Islamic education from the perspective of Tariq Ramadan’s thought and to propose an integrative strategy to bridge the gap between the principles of inclusivity and the implementation of the Islamic education curriculum. In general, Islamic education in Indonesia remains largely normative and formalistic, with a strong emphasis on religious identity, yet it provides insufficient space for social dialogue, critical reflection, and the appreciation of diversity. Tariq Ramadan offers an inclusive framework grounded in the principles of being faithful and being open and the notion of multiple belongings, which highlight the importance of cultivating a strong Muslim identity while remaining open, adaptable, and actively engaged in a pluralistic society. This study employs a descriptive qualitative approach through a literature review of Tariq Ramadan’s primary works, national curriculum documents, and relevant academic sources. This study finds that Tariq Ramadan’s concept of inclusivity is relevant to the notion of musawah (equality), which aligns with the objectives of the Project for Strengthening the Profile of Pancasila Students and Rahmatan lil ‘Alamin (P5RA). However, its implementation remains largely symbolic and has yet to engage with more complex and tangible social realities. This article identifies existing implementation gaps and proposes strategies for more effectively integrating inclusive principles into the Islamic education curriculum.